Determining an optimum zone radius for zone routing protocol (ZRP) based on node mobility - Khalid W. Al-Ani; Salman Yussof; Hussein M. Haglan; Hothefa Shaker; Linda Mahdi Alani (Institute of Advanced Engineering and Science, 2021)
Mobility is one of the important issues in Mobile Ad hoc Networks (MANET). By definition, MANET nodes are free to move around and this may cause difficulty in routing. MANET routing protocols must consider this factor when making routing decision. Zone Routing Protocol (ZRP) is a hybrid routing protocol, which utilizes the proactive and reactive routing protocols advantages. ZRP proactively maintains routing information within a routing zone, while reactively discovering routes to destinations beyond the routing zone. Since ZRP is based on the concept of routing zone, determining an optimum routing zone radius has the major impact on the performance of that protocol. In this research, we studied the effect of zone radius on the performance of ZRP with different levels of node mobility. Node mobility is defined using two different parameters: node speed and pause time. Based on the simulation results, ZRP protocol using zone radius of two provides the best packet delivery fraction, throughput and normalized routing load. However, a larger zone radius will provide a lower delay.